Oxygen Vacancies‐Rich TiO2/C Nanofibers with Boron, Nitrogen Dual‐Doping for Ultrafast Sodium Storage. Issue 28 (6th September 2022) - Huo, Jinghao; Ren, Yijie; Zhang, Guoqiang; Guo, Shouwu
Abstract: TiO2 is an intercalation pseudocapacitive material with low potential and minor structural changes during the sodium storage process. However, the intrinsic electronic conductivity and ionic diffusion kinetics are not unsatisfactory for ultrafast sodium storage. Defect engineering plays a pivotal part in improving the sodium storage kinetics of TiO2 anode materials. Now the common defect regulation methods are complicated. Herein, a simple NaBH4 reduction method is proposed to produce rich oxygen vacancies and boron doping in nitrogen‐doped TiO2 /C mesoporous nanofibers, and the finally obtained oxygen vacancies (OVs)‐rich TiO2 /C nanofibers (TC‐OVs) also build internal vertical channels. This particular structure of TC‐OVs favors fast transport for electrons and ions, resulting in ultrafast rate capability (156 mAh g −1, 2 A g −1 ) and long lifespan (139 mAh g −1, 1000 cycles, 1.0 A g −1 ). The inspiring sodium storage performance of TC‐OVs benefits from the high pseudocapacitance contribution (94%, 5.0 mV s −1 ). This work provides a method to adjust defects and structures of TiO2 electrode materials for ultrafast chemical energy storage. Abstract : Oxygen vacancies (OVs)‐rich TiO2 /C nanofibers (TC‐OVs) with B, N‐dual doping are fabricated by reducing N‐doped TiO2 /C mesoporous nanofibers (TC) with NaBH4, and vertical channels are formed in the TC‐OVs nanofibers during the NaBH4 treating process. The obtained TC‐OVs anode shows ultrafast rate capacity (156 mAh g −1, 2 A g −1 ) and long lifespan (139 mAh g −1, 1000 cycles, 1.0 A g −1 ).